Foraging behavior and ecology of the dog whelk nassarius pullus (Linne, 1758) on garbage-impacted beaches of Talim Bay, Batangas - Aloy, Alexander B.; Vallejo Jr., Benjamin M. (Quezon City Institute of Environmental Science & Meteorology, College of Science, University of the Philippines Diliman, 2010)
Sandy iintertidal habitats in the Philippines have received little attention in terms of the ecology of organisms particularly surface-dwelling macrofauna. Alternatively, most studies in this type of environmenrt in the global context investigated chronic and acute effects of oil spills, coastal fisheries, industrial sewage and heavy-metal contamination. Other environmental problems such as the effects of non-biodegradable garbage deposition (offshore litter) to intertidal faunal communities has not been commonly investigated. This study focused on the relative abundances and foraging behavior of the commonly occurring sandy intertidal-dwelling gastropod nassarius pullus in Talim Bay, Batangas which is periodically inundated by offshore garbage.
Thesis (Master of Science in Environmental Science)--University of the Philippines Diliman
Keywords: Nucella lapillus -- Philippines (Batangas City); Refuse and refuse disposal -- Philippines (Batangas City).